3D Master Toothguide according to L*, C*, and h* coordinates. Issue 5 (17th June 2014) - Gómez‐Polo, Cristina; Gómez‐Polo, Miguel; Martínez Vazquez De Parga, Juan Antonio; Celemin‐Viñuela, Alicia
ABSTRACT The purposes of this study are to describe the color coordinates of the 26 shade tabs of the 3D Master Toothguide according to their L*, C*, h* coordinates, and to calculate ΔEab*, ΔL*, ΔC*, and Δh* in the 26 shade tabs. The tooth color of 1361 maxillary central incisors was measured "in vivo" using a spectrophotometer. Tooth color was recorded following the 3D Master system and its corresponding L*, C*, h*color coordinates. Of the 325 shade tabs pairs compared a color difference ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj22vb6nrr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ΔEab*</alternatives>) of between 2.6 and 5.5 units was found in 9.54% (31 pairs). In 291 pairs (89.54%) there was color difference that exceeded the 5.5 units. Only 0.92% of the color differences (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj22vb6nn3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ΔEab*</alternatives>) were less than 2.6 units. The minimum color difference ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj22vb6nmj" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ΔEab*</alternatives>) found was 2.1 units and the maximum 45.0 units. The intervals in lightness, chroma, and hue groups between adjacent shade tabs were not uniform. In conclusion, this toothguide is clearly ordered regarding lightness or the L* coordinate. Most of the color differences between the 26 shade tabs of the 3D Master exceed the perceptible threshold of 2.6 units. Some clinical implications are as follows: the 26 shade tabs of the 3D Master Toothguide offer improvements as far as spatial arrangement is concerned. Thus, it is highly possible that the subjective visual color of the measurement would be correct. If there is a mistake when choosing the shade tab from the 3D Master guide there will quite probably be an unacceptable color difference from the clinical point of view. © 2014 Wiley Periodicals, Inc. Col Res Appl, 40, 518–524, 2015.